Studi deskriptif minat sosial pada remaja ditinjau dari latar belakang keluarga - Hultia Manani Syarqi; Sofa Amalia (Fakultas Psikologi, 2021)
Today’s teenagers spend more time with technology than interacting with people around them whereas adolescents should experience the process of learning and exploring and developing themselves through their surroundings and social environment to foster social interests. The purpose of this study is to describe the social interest of adolescents, especially regarding the family background using quantitative and qualitative approaches. The number of subjects in this study was 196 people with the criteria of the age is those in the age of 12-18 years. Data collection is conducted using the Social Interest Index (SII) instrument by Greever with a total of 32 items. The results of the study show that adolescents have moderate level social interest. There is no significant difference between social interest and the characteristics of the subjects or their family backgrounds.